2023
DOI: 10.1002/marc.202300012
|View full text |Cite
|
Sign up to set email alerts
|

Carbazolic Conjugated Microporous Polymers for Photocatalytic Organic Transformations

Abstract: Heterogeneous photocatalysis have been deemed as a versatile and colorful platform for exploring efficient transformation systems. Henceforth, the design of photocatalysts underpins a wide range of research interests. By virtue of synthetic versatility, stability, non‐toxicity, purely organic properties, tunable semiconductive structures, and remarkable visible‐light absorbance, conjugated microporous polymers (CMPs) have emerged as an attractive new class of semiconductor materials that show great potential f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 117 publications
0
4
0
Order By: Relevance
“…Conjugated microporous polymers (CMP) is a noteworthy material, similar to 3D COFs, but with differences in composition and synthesis. CMP combines extensive π-conjugation and a permanent microporous framework, exhibiting excellent photocatalytic performance in molecule and polymer synthesis, because of its strong light-capturing ability and narrow bandgap. , Hollow CMP microspheres (H-PPrlB-M MSs) were synthesized via Sonogashira–Hagihara cross-coupling polymerization, hydrofluoric acid etching, and alkyne–azide click grafting of azido-functionalized PEG . These microspheres serve as multiphase photocatalysts for PET-RAFT, allowing controlled polymerization of various polyacrylamides under mild conditions.…”
Section: Classification Of Aromatic Macrocyclic Photocatalystsmentioning
confidence: 99%
“…Conjugated microporous polymers (CMP) is a noteworthy material, similar to 3D COFs, but with differences in composition and synthesis. CMP combines extensive π-conjugation and a permanent microporous framework, exhibiting excellent photocatalytic performance in molecule and polymer synthesis, because of its strong light-capturing ability and narrow bandgap. , Hollow CMP microspheres (H-PPrlB-M MSs) were synthesized via Sonogashira–Hagihara cross-coupling polymerization, hydrofluoric acid etching, and alkyne–azide click grafting of azido-functionalized PEG . These microspheres serve as multiphase photocatalysts for PET-RAFT, allowing controlled polymerization of various polyacrylamides under mild conditions.…”
Section: Classification Of Aromatic Macrocyclic Photocatalystsmentioning
confidence: 99%
“…Porous organic frameworks (POFs) containing light elements have attracted more and more attention because of their unique and excellent properties . POFs generally include metal–organic frameworks (MOFs), covalent organic frameworks (COFs), conjugated microporous polymers (CMPs), porous aromatic frameworks (PAFs), and covalent triazine frameworks (CTFs). , Among them, COFs, characterized by discrete pores, are emerging highly ordered crystalline porous materials, mainly composed of light elements, such as H, B, C, and N, in the form of dynamic covalent bonds. Since the first synthesis of COF-1 and COF-5 by Yaghi and co-workers in 2005, scientists have explored different preparation strategies, such as solvothermal synthesis, ionothermal synthesis, and mechanochemical synthesis, to obtain functional COFs.…”
Section: Introductionmentioning
confidence: 99%
“…[43] Zhang et al summarized the application of metal-free and metal-containing carbazole CMPs in photocatalytic organic synthesis. [44] In this review, miscellaneous reported amorphous POPs are systematically classified, expecting to understand the current status of heterogeneous photocatalysts in the field of photocatalytic organic transformations (Figure 2). On the one hand, we present in detail the construction units of several common amorphous POPs.…”
Section: Introductionmentioning
confidence: 99%